(untitled) (Conference on English Language Teaching, 2023)
This research aimed to obtain empirical evidence of the effectiveness of pictures on Intensive Reading Class for Students Comprehension in D3. English Programs UNMER Malang. The objective to find challenges students’ faced in reading skill especially in Intensive Reading class in semester 1 (one). Whether reading skill could be improved by using pictures. This research is quantitative research by methodology experiment and conducted in two classes. Experimental group class A and control class group class B. Class A was taught by using pictures, while class B was not taught by using pictures. Author gave a reading test to gather the data. The mean of pretest in the experimental group is 61.37 and the control group is 58.5. The mean of post-test in the experimental group is 75.03 and the control group is 67.40. The obtained t-test is 5.76, whereas the t-table is 2.00 for α = 5%. The t-test value is higher than the t- table (5.76 > 2.00). Based on the result, picture effectiveness improved reading skill students in Intensive reading class for students in UNMER Malang. Writer suggests to the teacher and lectures, especially in reading class, to use pictures as one of the media in teaching learning for students.